Chloroplast genome structure and phylogenetic analysis of Glycosmis parviflora (Sims) Little 1948, a folk medicinal plant featured in Lingnan Region, China. Issue 6 (3rd June 2022) - Chen, Aimin; Li, Fang; Xie, Xuena; Huang, Rong; Tian, Enwei; Chao, Zhi
Abstract: Glycosmis parviflora is the most widely spread and the most morphologically varied species of Chinese Glycosmis, and its roots and leaves serve as folk medicines. We sequenced the complete chloroplast (cp) genome of G. parviflora . The cp genome obtained was a circular DNA molecule of 159, 825 bp in length, containing one large and one small single copy region (LSC and SSC) of 87, 517 and 18, 352 bp separated by a pair of 26, 978 bp inverted repeat regions (IRs). The overall GC content of the cp genome was 38.40%. The phylogenetic analysis revealed that Glycosmis was strongly supported as a monophyletic group belonging to Clauseneae, and G. parviflora was closely related to G. pentaphylla . The results will provide the basis for the further study of molecular markers and phylogeny of G. parviflora .